PD98059 Influences Immune Factors and Enhances Opioid Analgesia in Model of Neuropathy - Rojewska, Ewelina (PLoS One, 2015)
Neuropathic pain treatment remains challenging due to ineffective therapy and resistance to opioid analgesia. Mitogen-activated protein kinase kinase (MAPKK) have been identified as the crucial regulators of pro- and antinociceptive factors. We used PD98059, an inhibitor of the MAPKK family members MEK1/2. The aim of study was to examine the influence of single and/or repeated PD98059 on nociception and opioid effectiveness in neuropathy. Moreover, we examined how PD98059 influences selected members of cellular pathways and cytokines. The PD98059 (2.5 mcg) was intrathecally preemptively administered before chronic constriction injury (CCI), and then once daily for 7 days. Additionally, at day 7 after CCI the PD98059-treated rats received a single injection of opioids. Using Western blot and qRT-PCR techniques in PD98059-treated rats we analyzed the mRNA and/or protein level of p38, ERK1/2, JNK, NF-kappaB, IL-1beta, IL-6, iNOS and IL-10 in the lumbar spinal cord. Our results indicate that PD98059 has an analgesic effects and potentiates morphine and/or buprenorphine analgesia. Parallel we observed that PD98059 inhibit upregulation of the CCI-elevated p38, ERK1/2, JNK and NF-kappaB protein levels. Moreover, PD98059 also prevented increase of pro- (IL-1beta, IL-6, and iNOS) but enhances anti-nociceptive (IL-10) factors. Summing up, PD98059 diminished pain and increased the effectiveness of opioids in neuropathy. The inhibition of MEKs might inactivate a variety of cell signaling pathways that are implicated in nociception.